Breast state improvement by using the lymphatic drainage disposable bra pads - Kryzhanovskii, Edvard V.; Yavorsky, Alexander B.; Choong, Lim Kwong; Abdullah, Muslim Liew Bin (International Journal of Research in Medical Sciences, 2019)
Background: The health and good esthetic conditions of the breast are important indicators of women’s life quality. One factor that negatively affects this quality is the breast ptosis, associated with the sagging of the mammary glands due to tissue stretching and the loss of tissue and skin elasticity. New tools and methods able to improve the shape and beautiful contour of the breast are highly desirable. Methods: We investigated how the disposable bra pads by BAE International Inc., having the lymphatic drainage effect for the breast, influenced the female breast state. We applied two methods, the ultrasound elasticity imaging and the pattern recognition of the nipples position, to monitor the breast state dynamics in two groups of females, the study and control ones. Results: Preliminary results showed that both the breast elasticity and the pattern of nipple positions improved for females wearing the bra pads as compared to females wearing regular bras without pads (P<0.05 for the difference between the two groups of females). Conclusions: Overall, the bra pads by BAE can be considered as an effective tool encouraging metabolism by improving the flow of blood circulation and lymph in the breast.